Pengelolaan Dana Desa di Kecamatan Balong Kabupaten Ponorogo - Maretha Berlianantiya Muhammad Ridwan Eka Wardani (Universitas PGRI Madiun, 2019)
Poverty often occurs in rural areas rather than urban areas, low education which results in low quality of human resources and lack of access is often the cause of rural poverty. In addition, most of the economies of rural communities rely solely on the traditional agricultural sector. Various poverty reduction policies have been implemented, including village fund policies. This study aims to examine the management of village funds in the Balong sub-district of Madiun Regency with a case study in the villages of Tatung and Karangmojo villages covering the management of village funds in Tatung village and Karangmojo village. Balong Subdistrict and the impact of empowerment in the villages of Tatung and Karangmojo, Balong District. This research was conducted in Balong Subdistrict, Ponorogo Regency with a Case study in Tatung Village and Karangmojo Village with qualitative methods. In the village of Tatung village funds are managed as tourist villages with a focus on Paragliding tourist rides. Whereas in Karangmojo village it is used for Bumdes in the form of Lovebird birds, providing Gapoktan assistance, and infrastructure development.